Linguistic landscapes and educational spaces - Caprez-Krompàk, Edina; Fernández-Mallat, Víctor, 1981-; Meyer, Stephan, 1963- (New perspectives on language and education, 2022)
Drawing on insights from linguistics and semiotics, this book explores the linguistic landscape of the classroom and offers new perspectives on both linguistic landscape and educational sciences. The book brings together empirical studies conducted with two different foci: schoolscapes and the use of linguistic landscape as a pedagogical tool.